Amorphous copper-based nanocluster loaded on carbon nanotube as well as preparation method and application of amorphous copper-based nanocluster

By loading amorphous copper-based nanoclusters on carbon nanotubes, using simple chelation co-precipitation method and inorganic ions as ligands, the problems of low catalytic activity and selectivity, complex preparation process and high cost in the prior art are solved, and an efficient electrocatalytic nitrate reduction reaction is achieved.

CN119710781APending Publication Date: 2025-03-28XIHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411806541.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art has low catalytic activity and selectivity in electrochemical nitrate reduction reactions, and the preparation process of copper-based nanoclusters is complicated. The use of organic ligands has high cost and toxicity problems, and it is difficult to control its crystal form.

Method used

The crystal structure of the copper nanoclusters was prepared by loading amorphous copper-based nanoclusters on carbon nanotubes using a simple chelation coprecipitation method at room temperature, using inorganic ions such as OH- and Cl- as ligands, using sodium citrate salts.

Benefits of technology

It realizes the rapid and economical preparation of highly active and selective amorphous copper-based nanoclusters at room temperature, reduces the production cost and toxicity, and can be effectively used in electrocatalytic nitrate reduction reactions, with good processing effect and reusable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710781A_ABST
    Figure CN119710781A_ABST
Patent Text Reader

Abstract

The invention discloses an amorphous copper-based nanocluster loaded on a carbon nano tube as well as a preparation method and application of the amorphous copper-based nanocluster. The nanocluster is an amorphous Cu (OH) Cl nanocluster a-Cu (OH) Cl / CNTs loaded on the carbon nano tube; the method comprises the following steps: S1, ultrasonically dispersing anhydrous CuCl2 and carbon nanotubes into an ethylene glycol solution; s2, adding trisodium citrate into the mixed solution, then dropwise adding a NaOH solution, and performing magnetic stirring, suction filtration and drying to obtain a sample. Compared with a traditional method for preparing the copper nanocluster through a complex method with harsh reaction conditions, the copper nanocluster is synthesized through a simple chelating coprecipitation method at the room temperature, and industrial large-scale production is facilitated; compared with a traditional method for preparing the copper nanocluster through coordination of an organic reagent and copper ions, the cost is lower, and the toxicity is lower; the crystal structure of the copper nanocluster can be controllably adjusted through the sodium citrate salt, and the method is simple and easy to implement; the catalyst can be well applied to nitrate water pollutant treatment, has a good treatment effect, and can be repeatedly used for multiple times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention belongs to the technical field of materials, and particularly relates to an amorphous copper-based nanocluster supported on a carbon nanotube, and a preparation method and application thereof. Background technology:

[0002] The widespread use of nitrogen fertilizers and high nitrate concentrations worldwide The large amount of industrial wastewater discharged makes the source of nitrate in the natural environment extremely rich. Secondly, the World Health Organization requires that NO3 - The content is less than 10mg NL -1 , excessive nitrates can easily cause human diseases. Therefore, reducing nitrate pollutants in the environment to ammonia with higher added value through electrochemical methods is of great significance for achieving nitrogen recycling and controlling water pollution. However, the electrochemical nitrate reduction reaction (NITRR) to produce ammonia is an 8-electron and 9-proton transfer reaction, and its reaction kinetics are slow. In addition, the competitive hydrogen evolution reaction (HER) and various nitrogen-containing byproducts (such as NO2 - The formation of N2 and N2, etc., leads to extremely low selectivity and efficiency of NITRR. Therefore, designing and developing electrocatalysts with high activity and selectivity to realize electrochemical NITRR ammonia synthesis remains a major challenge.

[0003] Copper (Cu)-based nanoclusters have high catalytic activity and selectivity for electrochemical NITRR ammonia synthesis due to their abundant active sites, unique outer electron configuration and ability to inhibit HER. In addition, compared with crystalline metal materials, amorphous metal materials show better catalytic ability in electrocatalytic ammonia synthesis. This advantage stems from the presence of a large number of low-coordinated atoms in amorphous metal-based electrocatalysts, which increases the number of catalytic sites and thus improves their performance. However, at present, Cu-based nanoclusters are mainly prepared by coordination modification of copper ions with organic ligands (such as 4-mercaptophenylboronic acid, thiol and triphenylamine, etc.), which has the disadvantages of complex preparation process and expensive and toxic organic ligands used. In addition, it is still difficult to achieve controllable regulation of the crystal form of copper-based nanoclusters at the experimental level. Therefore, the controllable preparation of supported amorphous copper-based nanoclusters by a simple and mild method remains a problem to be solved.

[0004] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention:

[0005] The purpose of the present invention is to provide an amorphous copper-based nanocluster supported on a carbon nanotube and a preparation method and application thereof, thereby overcoming the defects in the above-mentioned prior art.

[0006] In order to achieve the above object, the present invention provides an amorphous copper-based nanocluster supported on a carbon nanotube, wherein the amorphous copper-based nanocluster is a supported amorphous Cu(OH)C1 nanocluster a-Cu(OH)C1 / CNTs.

[0007] The present invention also provides a method for preparing the above-mentioned amorphous copper-based nanoclusters supported on carbon nanotubes, comprising the following steps:

[0008] S1: Ultrasonic dispersion of anhydrous CuCl2 and carbon nanotubes into ethylene glycol solution;

[0009] S2: trisodium citrate was added to the mixed solution, followed by dropwise addition of NaOH solution, magnetic stirring, suction filtration, and drying to obtain a sample.

[0010] Furthermore, preferably, in step S1, the mass ratio of anhydrous CuCl2 to the volume ratio of ethylene glycol solution is 5-60 g / L, and the mass ratio of carbon nanotubes to the volume ratio of ethylene glycol solution is 0.5-20 g / L.

[0011] Furthermore, preferably, the temperature of the ultrasound in step S1 is 20-40° C., and the frequency is 20-50 kHz.

[0012] Furthermore, preferably, in step S2, the mass ratio of trisodium citrate to the volume ratio of the ethylene glycol solution is 1-5 g / L, and the concentration of the NaOH solution is 0.1-5 mol / L.

[0013] Furthermore, preferably, the magnetic stirring time in step S2 is 5 min to 300 min, and the drying temperature is 40 to 100°C.

[0014] The present invention also provides an application of the amorphous copper-based nanoclusters supported on the carbon nanotubes, which is used for electrocatalytic nitrate synthesis of ammonia and in the treatment of nitrate body pollutants.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] (1) Compared with the traditional method of preparing copper nanoclusters by complex and harsh reaction conditions, the present invention synthesizes copper nanoclusters by a simple chelate co-precipitation method at room temperature, which is conducive to industrial large-scale production;

[0017] (2) The present invention uses inorganic ions (such as OH - and Cl -) as a ligand to prepare ultrafine amorphous Cu(OH)Cl nanoclusters, which is lower in cost and less toxic than the traditional method of preparing copper nanoclusters by coordinating organic reagents (such as 4-mercaptophenylboronic acid, thiol and triphenylamine) with copper ions;

[0018] (3) The present invention can controllably adjust the crystal structure of copper nanoclusters by sodium citrate, which is simple and easy to implement;

[0019] (4) The supported amorphous Cu(OH)Cl nanoclusters of the present invention can be well applied in the treatment of nitrate water pollutants, have good treatment effects, and can be used repeatedly. Description of the drawings:

[0020] Figure 1 This is a schematic diagram of the process for preparing supported amorphous Cu(OH)Cl nanoclusters according to Example 1 of the present invention;

[0021] Figure 2 a is a transmission electron microscope (TEM) image of the supported amorphous Cu(OH)Cl nanoclusters prepared in Example 1 of the present invention;

[0022] Figure 2 b. Figure 2 c is a high-resolution transmission electron microscopy (HR-TEM) image of the supported amorphous Cu(OH)Cl nanoclusters prepared in Example 1 of the present invention;

[0023] Figure 2 d is a transmission electron microscope (TEM) image of the supported crystalline Cu2(OH)3Cl2 nanoclusters prepared in the comparative example of the present invention;

[0024] Figure 2 e. Figure 2 f is a high-resolution transmission electron microscopy (HR-TEM) image of the supported crystalline Cu2(OH)3Cl2 nanoclusters prepared in the comparative example of the present invention;

[0025] Figure 3 X-ray diffraction (XRD) patterns of the supported amorphous Cu(OH)Cl nanoclusters prepared in Example 1 of the present invention and the supported crystalline Cu2(OH)3Cl2 nanoclusters prepared in the comparative example;

[0026] Figure 4 This is an X-ray photoelectron spectroscopy (XPS) graph of the supported amorphous Cu(OH)Cl nanoclusters prepared in Example 1 of the present invention;

[0027] Figure 5 This is an infrared spectrum of the supported amorphous Cu(OH)Cl nanoclusters prepared in Example 1 of the present invention;

[0028] Figure 6 This is a linear sweep voltammetric test graph of the electrocatalytic nitrate reduction test of the supported amorphous Cu(OH)Cl nanoclusters prepared in Example 1 of the present invention;

[0029] Figure 7 This is a chronoamperometric test diagram of the electrocatalytic nitrate reduction test of the supported amorphous Cu(OH)Cl nanoclusters prepared in Example 1 of the present invention;

[0030] Figure 8 This is a test diagram of the cyclic stability of the supported amorphous Cu(OH)Cl nanoclusters prepared in Example 1 of the present invention in the electrocatalytic nitrate reduction test. Specific implementation method:

[0031] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.

[0032] A brief summary of one or more aspects is given below to provide a basic understanding of these aspects. This summary is not an exhaustive overview of all conceived aspects, and is neither intended to identify the key or critical elements of all aspects nor to define the scope of any or all aspects. Its only purpose is to give some concepts of one or more aspects in a simplified form as a prelude to a more detailed description that will be given later.

[0033] Embodiment 1:

[0034] A method for preparing supported amorphous Cu(OH)Cl nanoclusters (a-Cu(OH)Cl / CNTs) comprises the following steps:

[0035] s1: 100 mg of anhydrous CuCl2 and 20 mg of carbon nanotubes (CNTs) were ultrasonically dispersed in 20 mL of ethylene glycol (EG) solution at a temperature of 25 °C and a frequency of 30 kHz;

[0036] S2: Add 20 mg of trisodium citrate to the mixed solution, then drop 10 mL of 0.2 mol / L NaOH solution, stir magnetically for 10 min, filter, and dry at 60° C. to obtain a sample.

[0037] Embodiment 2:

[0038] A method for preparing supported amorphous Cu(OH)Cl nanoclusters (a-Cu(OH)Cl / CNTs) comprises the following steps:

[0039] s1: 80 mg of anhydrous CuCl2 and 15 mg of carbon nanotubes (CNTs) were ultrasonically dispersed in 20 mL of ethylene glycol (EG) solution at a temperature of 25 °C and a frequency of 30 kHz;

[0040] S2: Add 20 mg of trisodium citrate to the mixed solution, then drop 8 mL of 0.2 mol / L NaOH solution, stir magnetically for 10 min, filter, and dry at 60° C. to obtain a sample.

[0041] Embodiment 3:

[0042] A method for preparing supported amorphous Cu(OH)Cl nanoclusters (a-Cu(OH)Cl / CNTs) comprises the following steps:

[0043] S1: 60 mg of anhydrous CuCl2 and 15 mg of carbon nanotubes (CNTs) were ultrasonically dispersed in 20 mL of ethylene glycol (EG) solution at a temperature of 25 °C and a frequency of 30 kHz;

[0044] S2: Add 20 mg of trisodium citrate to the mixed solution, then drop 9 mL of 0.2 mol / L NaOH solution, stir magnetically for 10 min, filter, and dry at 60° C. to obtain a sample.

[0045] Comparative Example:

[0046] The difference from Example 1 is that in step S2, trisodium citrate is not added to the mixed solution, and the obtained sample is a supported crystalline Cu2(OH)3Cl2 nanoclusters (c-Cu2(OH)3Cl2 / CNTs).

[0047] The above Example 1 and the comparative example were characterized in various aspects, and the results were as follows:

[0048] Figure 2 a is a transmission electron microscope (TEM) image of the supported amorphous Cu(OH)Cl nanoclusters (a-Cu(OH)Cl / CNTs) prepared in Example 1 of the present invention, from which it can be seen that the supported amorphous Cu(OH)Cl nanoclusters are uniformly distributed on the carbon nanotubes, and the average particle size is about 9 nm;

[0049] Figure 2 b. Figure 2 c is a high-resolution transmission electron microscope (HR-TEM) image of the supported amorphous Cu(OH)Cl nanoclusters (a-Cu(OH)Cl / CNTs) prepared in Example 1 of the present invention, from which it can be seen that the Cu(OH)Cl nanoclusters are amorphous structures;

[0050] Figure 2d is a transmission electron microscope (TEM) image of the supported crystalline Cu2(OH)3Cl2 nanoclusters (c-Cu2(OH)3Cl2 / CNTs) prepared in the comparative example of the present invention, from which it can be seen that the average particle size of the supported crystalline Cu2(OH)3Cl2 nanoclusters on the carbon nanotubes is about 15 nm;

[0051] Figure 2 e. Figure 2 f is a high-resolution transmission electron microscope (HR-TEM) image of the supported crystalline Cu2(OH)3Cl2 nanoclusters (c-Cu2(OH)3Cl2 / CNTs) prepared in the comparative example of the present invention. It can be seen from the figure that the supported crystalline Cu2(OH)3Cl2 nanoclusters have obvious lattice fringes, indicating that they are crystalline structures;

[0052] Figure 3 The X-ray diffraction (XRD) diagrams of the supported amorphous Cu(OH)Cl nanoclusters (a-Cu(OH)Cl / CNTs) prepared in Example 1 of the present invention and the supported crystalline Cu2(OH)3Cl2 nanoclusters (c-Cu2(OH)3Cl2 / CNTs) prepared in the comparative example, the abscissa represents the diffraction angle, and the ordinate represents the diffraction intensity. It can be seen from the figure that when trisodium citrate is not added, supported crystalline Cu2(OH)3Cl2 nanoclusters (c-Cu2(OH)3Cl2 / CNTs) with obvious Cu2(OH)3Cl2 diffraction peaks are obtained. After sodium citrate is added, no diffraction peaks belonging to copper-based nanoclusters are observed, indicating that copper-based amorphous nanoclusters (a-Cu(OH)Cl / CNTs) are obtained;

[0053] Above Figure 2 a-2f, Figure 3 The addition of trisodium citrate on the surface plays a vital role in the formation of amorphous Cu(OH)Cl nanoclusters (a-Cu(OH)Cl / CNTs), and the crystal structure of copper nanoclusters can be controllably adjusted by sodium citrate salt;

[0054] Figure 4 This is an X-ray photoelectron spectrum (XPS) of the supported amorphous Cu(OH)Cl nanoclusters (a-Cu(OH)Cl / CNTs) prepared in Example 1 of the present invention. It can be seen from the figure that the main existing form of the Cu element in the Cu(OH)Cl nanoclusters (a-Cu(OH)Cl / CNTs) is +2 valence;

[0055] Figure 5This is an infrared spectrum of the supported amorphous Cu(OH)Cl nanoclusters (a-Cu(OH)Cl / CNTs) prepared in Example 1 of the present invention. It can be seen from the figure that HO…C1 and Cu-OH bonds exist in the sample;

[0056] The supported amorphous Cu(OH)Cl nanoclusters (a-Cu(OH)Cl / CNTs) prepared in Example 1 were subjected to an electrocatalytic nitrate reduction test, and the test method was as follows: a three-electrode working system was used for the test, wherein a Pt sheet was used as a counter electrode, Ag / AgCl was used as a reference electrode, and carbon paper coated with a-Cu(OH)Cl / CNTs sample was used as a working electrode.

[0057] First, perform a linear sweep voltammetry test, such as Figure 6 As shown in the figure, it can be seen that 0.1M Na2SO4+500ppmNO3 - The current density generated in the electrolyte is significantly higher than that generated by 0.1M Na2SO4 electrolyte, proving the presence of NO3 - Reduction reaction.

[0058] Then, a chronoamperometric test was performed to determine the ammonia content by a colorimetric method, and the ammonia yield and Faraday efficiency were calculated based on the experimental results, such as Figure 7 As shown, a-Cu(OH)Cl / CNTs has the maximum ammonia yield (254.40 μg·h-1mg-1cat.) and Faraday efficiency (77.09%) when the applied potential is -0.9 V (relative to the reversible hydrogen electrode), indicating that a-Cu(OH)Cl / CNTs has good electrocatalytic performance in nitrate reduction to produce ammonia.

[0059] Then the cyclic stability test of Cu(OH)Cl nanocluster catalyst was carried out. Figure 8 It can be seen that after 10 cycles of testing, the Faradaic efficiency is always maintained above 70%, indicating that the a-Cu(OH)Cl / CNTs catalyst has good stability.

[0060] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. An amorphous copper-based nanocluster supported on a carbon nanotube, characterized in that: The amorphous copper-based nanoclusters are amorphous Cu(OH)Cl nanoclusters a-Cu(OH)Cl / CNTs supported on carbon nanotubes.

2. A method for preparing the amorphous copper-based nanoclusters supported on carbon nanotubes according to claim 1, characterized in that: The following steps are involved: S1: Ultrasonic dispersion of anhydrous CuCl2 and carbon nanotubes into ethylene glycol solution; S2: trisodium citrate was added to the mixed solution, followed by dropwise addition of NaOH solution, magnetic stirring, suction filtration, and drying to obtain a sample.

3. The method for preparing the amorphous copper-based nanoclusters supported on carbon nanotubes according to claim 1 according to claim 2, characterized in that: In the step S1, the mass ratio of anhydrous CuCl2 to the volume ratio of the ethylene glycol solution is 5-60 g / L, and the mass ratio of the carbon nanotubes to the volume ratio of the ethylene glycol solution is 0.5-20 g / L.

4. The method for preparing the amorphous copper-based nanoclusters supported on carbon nanotubes according to claim 1 according to claim 2, characterized in that: The temperature of the ultrasound in step S1 is 20-40° C., and the frequency is 20-50 kHz.

5. The method for preparing the amorphous copper-based nanoclusters supported on carbon nanotubes according to claim 1 according to claim 2, characterized in that: In step S2, the mass ratio of trisodium citrate to the volume ratio of ethylene glycol solution is 1-5 g / L, and the concentration of NaOH solution is 0.1-5 mol / L.

6. The method for preparing the amorphous copper-based nanoclusters supported on carbon nanotubes according to claim 1 according to claim 2, characterized in that: The magnetic stirring time in step S2 is 5 min to 300 min, and the drying temperature is 40 to 100° C.

7. An application of the amorphous copper-based nanoclusters supported on carbon nanotubes according to claim 1, characterized in that: Used for electrocatalytic synthesis of ammonia from nitrate.